PENINGKATAN KEMAMPUAN KONSEP MATEMATIKA MELALUI MEDIA BERMAIN STICK ANGKA PADA ANAK - Mayasari, Rini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is conducted by teachers who do not implement the method of playing in learning process of mathematics concept using media that can stimulate the development of mathematics concept of children so that group A children in ABA VI kindergarten still have not developed mathematics concept well, less able to manage class. The general problem of this research is whether by the method of playing stick figures can improve cognitive development in children group A in kindergarten Asyiyah Bustanul Atfhal VI? The purpose of this study is to improve the ability of mathematical concepts through the method of playing media stick figures. An assessment aspect of mathematical concepts observed is the ability of children to sort, group, and distinguish objects according to size, shape, and color. This research uses form of Class Action Research and descriptive method. Research subjects are teachers and children group A, Based on the results of research that has been done and the results of data analysis, it can generally be concluded that the improvement of the ability of mathematical concepts can be done through the method of playing through media Stick figures in children in kindergarten ABA VI . It can be concluded Planning, Implementation and Improvement ability of mathematics concept of child of A class in kindergarten ABA Â VI is good. Keywords: Mathematical Concepts, Playing Methods via Stick Media Numbers